Type specimens of Tamarix (Tamaricaceae) described by Josef Franz Freyn in 1903 - Villar García, Jose Luis; Juan, Ana; Alonso, Maria Angeles; Crespo, Manuel Benito (Phytotaxa, 2014)
Five Tamarix taxa were described in Freyn’s posthumous publication (Freyn 1903): Tamarix askabadensis Freyn (1903: 1059), Tamarix karakalensis Freyn (1903: 1060), T. karakalensis var. scoparia Freyn (1903: 1062), T. karakalensis var. verrucifera Freyn (1903: 1062), and T. karakalensis var. myriantha Freyn (1903: 1062). This publication comprised an enumeration of the plants collected by Paul Sintenis in “Tauria, 1900–1901” (in the Sintenis’s voucher labels as “Iter transcaspico-persicum 1900–1901”), by Ove Paulsen in “regione caspica, transcaspica, praesertium in altiplanitie Pamir, 1898–1899”, and by Victor Ferdinand Brotherus “in Turkestania, 1896”. However, all Tamarix taxa treated in that work belong to those collected by Sintenis. It is important to point out that Sintenis was mostly a plant collector who sold his vouchers to many different herbaria: ANK, BHUPM, BREM, G, GH, HAC, JE, LD, PAL, PR, TUB, VT, W, WAG, and WU (acronyms according to Thiers 2014). However, his personal herbarium (ca. 80000 vouchers of 18000 species) was acquired by the Herbarium of the Botanical Museum of Lund (LD) in 1921–1922 (Patrik Frödén pers. comm.).